2017
DOI: 10.3390/ijms18040788
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles Contribute to the Bystander Effect of DNA Damage

Abstract: Genotoxic treatments elicit DNA damage response (DDR) not only in cells that are directly exposed but also in cells that are not in the field of treatment (bystander cells), a phenomenon that is commonly referred to as the bystander effect (BE). However, mechanisms underlying the BE remain elusive. We report here that etoposide and ultraviolet (UV) exposure stimulate the production of microvesicles (MVs) in DU145 prostate cancer cells. MVs isolated from UV-treated DU145 and A431 epidermoid carcinoma cells as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Annexin V, which neutralizes the formation of MVs derived from UV-treated cells, significantly reduced the MV-associated BE activities. The presented results provide evidence supporting that MVs are a source of the DNA damage-induced bystander effect [ 13 ].…”
supporting
confidence: 65%
“…Annexin V, which neutralizes the formation of MVs derived from UV-treated cells, significantly reduced the MV-associated BE activities. The presented results provide evidence supporting that MVs are a source of the DNA damage-induced bystander effect [ 13 ].…”
supporting
confidence: 65%
“…However, pretreatment of DU145 naive cells with an ATM (KU55933) inhibitor does not affect the bystander effect of isolated MVs from etoposide treated cells. This study shows that MVs are one of the bystander effect sources [14].…”
Section: Bystander Effectmentioning
confidence: 66%
“…It could be the bystander effect of radiotherapy, that is, the same effect of radiotherapy on cells, tissues or organs in non-irradiated areas ( Wang et al, 2015 ; Fu et al, 2020 ). After irradiation, cells in the irradiated area can secrete cytokines, small molecular metabolites, exosomes or microvesicles containing various substances, and other media ( Lin et al, 2017 ; Ariyoshi et al, 2019 ; Ni et al, 2020 ; Mukherjee et al, 2021 ), resulting in metabolic disorders, apoptosis, endoplasmic reticulum and golgi dysfunction of cells in non-irradiated areas ( Yakovlev, 2015 ; Jella et al, 2018 ; Mladenov et al, 2018 ; Dong et al, 2020 ; Heeran et al, 2021 ; Yang et al, 2021 ). Earlier studies reported elevated levels of CRP in circulating blood, and splenic cells exhibited enhanced levels of oxidative stress and increased apoptosis after cranial irradiation in rats ( El-Din et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%